Filmfare and the question of Bengali cinema (1955–65). Issue 2 (3rd April 2018) - Basu, Anustup
ABSTRACT: This essay is a critical genealogy of Bengali cinema roughly between 1955 and 1965, as the story unfolded in the pages of Filmfare, the preeminent mainstream cinema periodical in India. It locates the question of Bengali cinema in a greater textualization of a burgeoning Indian film in the world. The account covers three lines of vision, in terms of how Bombay, as film capital, was looking to Calcutta to supply a literary-reformist guidance to an emerging national form, how Calcutta was conversing with Europe and America in a manner that almost totally bypassed the pan-Indian scenario, and how the west was also frequently looking at the cinematic universe of Satyajit Ray and his peers without any necessary refractive mediation by an all-India prism. Along the way, the essay also revisits crucial moments in the history of the Bengali film industry, both in terms of its commercial and artistic accomplishments as well as its failures to set up regular lines of exchange with other major industries like Bombay and Madras, as well as neighbours like Orissa, Assam, Burma, and what eventually became the independent country of Bangladesh.